Public Private Partnership (PPP) Project Performance in Malaysia: Identification of Issues and Challenges - Hasnan Hashim; Adi Irfan Che-Ani; Kharizam Ismail (International Journal of Supply Chain Management, 2017)
Public Private Partnership (PPP) in Malaysia as an innovative procurement mechanism aims to undertake the public sector infrastructure project construction in order to overcome the weaknesses of conventional system. PPP is seen significantly viable to enhance the quality of public services and stimulate economic growth. After the decades of its implementation, many arguments have been reported along the lively growth of PPP project development. Within that context, this study provides a review of issues and challenges for PPP pertaining to project performance in Malaysia. The objective of this study is to highlight the loophole of PPP implementation in Malaysia through a qualitative approach. A qualitative approach was used to analyse contextual literature review and to investigate four selected performance measurement models as the precedent study to provide a basis for improvement of PPP in Malaysia. The findings showed that the issues and challenges were almost similar between the literature and selected models in which the guideline / framework, Key Performance Indicator (KPI), risk allocation, efficiency flexibility were perceived as dominant issues. Apart from that, a technical factor had proven as the most threated factor that could hinder the implementation of PPP project in Malaysia. Hence, the structure of PPP model should be more viable towards the stakeholders by developing a clear, realistic and concise guideline in order to improve the service delivery performance and return value for money.